Transesterification of Palm Olein by Immobilised Microbial Lipases - Sidek, Hamidah (1996)
Enzymatic transesterification of palm olein in organic solvent was studied. The enzyme was first immobilised to celite, lyophilised for 4 h and then added to a reaction medium composed of water-saturated hexane containing of 10% (w/v) palm olein. The catalytic performance of the enzyme was evaluated by determining changes in the triglycerides (TG) composition and concentration by reverse-phase high performance liquid chromatography (RP-HPLC) and the formation of free fatty acids (FF A) by titration, respectively. For Candida rugosa lipase, the optimal water content was controlled by lyophilisation of the lipase preparation for 4 h. The addition of water to the dried immobilised preparation shifted the reaction equilibrium to favour net hydrolysis. Of the commercially available lipases that were investigated, lipases from Pseudomonas sp. and the lipase from Rhizomucor miehei resulted in the highest extent of transesterification. Besides palm olein, palm kernel olein and coconut oil showed some changes in the triglyceride composition after transesterification process. Changes in the palm olein concentration in the range 5- 1 00% increased the degree of transesterification of the immobilised Pseudomonas sp. and declined with the R. miehei lipase. The maximum enzyme activity was reached at an enzyme loading of 0.40% (w/w). The optimum temperature for trans esterification by immobilised Pseudomonas sp. lipase was 48°C. Hexane, cyclohexane and isooctane were found to be particularly useful organic solvents in the transesterification process. Water-saturated hexane system can be replaced by either dimethysulfoxide- or dimethylformamide-saturated hexane. Methanol was not suitable for the transesterification process. In all cases, the transesterification process resulted in the formation of PPP (tripalmitin), a trisaturated triglyceride initially undetected in the oil, and minor increases in the concentration of 000, OOL, OLL, SOS, where P, 0, L and S are palmitic, oleic, linoleic and stearic acid, respectively thus increasing the slip melting point of the final product.